A 3D printed high-wear-resistant denture and preparation method thereof
The high wear-resistant denture materials composed of zirconia/titanium oxide nanocomposite rods and silver-doped alumina particles were prepared through 3D printing technology, which solved the problem of insufficient wear resistance and bacteriostatic properties of existing denture materials, achieved higher wear resistance and bacteriostatic properties, and extended the service life of dentures.
Patent Information
- Application Number
- CN202411068120.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-08-06
AI Technical Summary
Existing denture materials have shortcomings in wear resistance and antibacterial properties, resulting in increased wear and an increased risk of oral infection during long-term use.
3D printing technology is used to prepare high wear-resistant denture materials composed of zirconia/titanium oxide nanocomposite rods and silver-doped alumina particles, and the material's wear resistance and bacteriostatic resistance are improved through nanocomposite and multi-stage structural design.
It significantly improves the wear resistance and antibacterial properties of dentures, extends the service life of dentures, reduces the risk of oral complications, and improves the quality of life of patients.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of denture materials, and in particular to a 3D printed high-wear-resistant denture and a preparation method thereof. Background Art
[0002] As an oral prosthesis, dentures must not only have good biocompatibility and mechanical properties, but also meet the requirements of wear resistance and antibacterial properties during long-term use. Denture materials are subjected to repeated stress and wear during chewing, so they must have sufficient hardness and wear resistance to maintain the stability of the occlusal relationship and the integrity of the restoration. At the same time, the oral environment is complex and prone to the breeding of a variety of pathogenic microorganisms, leading to oral infections and denture-related inflammation. Therefore, denture materials also need to have certain antibacterial properties to effectively inhibit the attachment and reproduction of bacteria and reduce the risk of oral complications.
[0003] At present, although traditional denture materials can meet the needs of patients to a certain extent, they often suffer from problems such as increased wear and morphological changes during long-term chewing, which seriously affect the service life of dentures and the comfort of patients. At the same time, the oral cavity is a breeding ground for bacteria, and bacteria are easily attached to the surface of dentures, causing oral infections and other complications, posing a threat to the oral health of patients. Therefore, it is necessary to develop a new type of highly wear-resistant denture that has both high wear resistance and antibacterial properties to meet the needs of high-performance dentures. Summary of the invention
[0004] (1) Technical issues solved
[0005] The purpose of the present invention is to provide a 3D printed high-wear-resistant denture and a preparation method thereof, so as to solve the problem that the current dentures are insufficient in wear resistance and antibacterial performance.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A 3D printed high-wear-resistant denture is prepared from the following components in parts by weight: 25 to 40 parts of zirconium oxide / titanium oxide nanocomposite rods, 10 to 20 parts of silver-doped alumina particles, 40 to 75 parts of nano zirconium oxide powder, 2 to 5 parts of sintering aids, 6 to 12 parts of adhesives, 3 to 5 parts of dispersants, 15 to 25 parts of solvents, and 0.3 to 1.2 parts of pigments.
[0009] The average length of the zirconium oxide / titanium oxide nanocomposite rods is 300-550 nm, and the average diameter is 80-120 nm.
[0010] The zirconium oxide / titanium oxide nanocomposite rods are composed of zirconium oxide nanorods and titanium oxide particles uniformly distributed on the surface thereof, forming a structure similar to corn kernels on a corn cob. The diameter of the titanium oxide particles is 10-20 nm.
[0011] The titanium oxide particles are in-situ grown on the zirconium oxide nanorods under a hydrothermal reaction.
[0012] The interface between the zirconium oxide and the titanium oxide is a semi-coherent interface.
[0013] The highly wear-resistant denture contains a silver-doped alumina phase, which is produced by silver-doped alumina particles during the sintering process, and the silver-doped atomic percentage is 0.2-0.6 at.%.
[0014] The silver-doped aluminum oxide phase contains a twin structure.
[0015] The interface between the silver-doped aluminum oxide phase and the zirconium oxide phase contains a coherent interface.
[0016] Furthermore, the preparation method of the zirconium oxide / titanium oxide nanocomposite rod is as follows: after 4 to 9 parts of tetrabutyl titanate and 80 to 100 parts of anhydrous ethanol are mixed evenly by weight, 30 to 50 parts of zirconium oxide nanorods are added thereto, and a uniform mixed solution is obtained after magnetic stirring for 30 to 60 minutes, and then the mixed solution is added to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 200 to 250° C. for 12 to 20 hours for hydrothermal reaction. After the reaction is completed, the mixed solution is filtered, washed with deionized water three times, and the filtered product is dried in a vacuum oven at 60 to 80° C. for 10 to 20 hours to obtain the zirconium oxide / titanium oxide nanocomposite rod.
[0017] Furthermore, the preparation method of the zirconium oxide nanorods is as follows: by weight, 10 to 18 parts of zirconium oxychloride, 2 to 4 parts of cyclohexane, 3 to 8 parts of polyoxyethylene coconut oil ester and 30 to 45 parts of a sodium hydroxide solution with a mass fraction of 10% are mixed, and the mixture is stirred for 3 to 8 hours under magnetic stirring to obtain a precipitated mixed solution, and then the mixed solution is centrifuged, the precipitate is dried at room temperature, and then heat-treated at 800 to 900° C. for 3 to 7 hours in an air atmosphere, and the zirconium oxide nanorods are obtained after cooling.
[0018] The present invention designs zirconia / titanium oxide nanocomposite rods as a reinforcing material for 3D printed dentures, aiming to improve the wear resistance and antibacterial properties of the dentures while maintaining good biocompatibility. Zirconia ceramics can provide a good wear resistance foundation for composite materials due to their excellent mechanical properties, such as high hardness, high strength and high toughness. Nanoscale zirconia nanorods have higher specific surface area and surface energy, which can enhance the bonding with the denture matrix material and further improve the overall mechanical properties. At the same time, titanium oxide particles are evenly distributed on the surface of zirconia nanorods to form a multi-level structure similar to corn cobs. This unique structure is expected to further enhance the wear resistance of the denture material. The semi-coherent interface formed between zirconia and titanium oxide is conducive to interface bonding and stress transfer, thereby improving the wear resistance of the composite material. In addition, both zirconia and titanium oxide themselves have certain antibacterial properties, which can inhibit the attachment and reproduction of bacteria on the denture surface to a certain extent. The nanoscale composite structure provides a higher specific surface area and more active sites, which may help enhance the antibacterial effect of the material, but further research is still needed to confirm its antibacterial mechanism and effect. At the same time, the good biocompatibility of zirconium oxide and titanium oxide can reduce the stimulation and adverse reactions of dentures to oral tissues. In general, the zirconium oxide / titanium oxide nanocomposite rods designed by the present invention are used as reinforcement materials for 3D printed dentures. Through the design of nanocomposite and multi-level structure, they strive to improve the wear resistance and antibacterial properties of dentures, while maintaining good biocompatibility, providing new possibilities for the development of high-performance dentures. However, its actual effect still needs to be verified through further experimental research and performance evaluation, and the design and preparation process of the composite material should be optimized according to the results to give full play to the potential of zirconium oxide / titanium oxide nanocomposite rods as reinforcement materials.
[0019] Furthermore, the preparation method of the silver-doped alumina particles is as follows: in parts by weight, 2 to 4 parts of silver acetate and 120 parts of N-methylpyrrolidone are mixed and ultrasonically dispersed for 15 to 30 minutes to obtain a uniform dispersion of silver acetate in N-methylpyrrolidone; subsequently, 12 to 20 parts of methylaluminoxane are slowly added to the above-mentioned mixed solution, and then magnetically stirred for 30 to 60 minutes to obtain a silver-doped alumina precursor solution; the silver-doped alumina precursor solution is transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, sealed, and hydrothermally reacted at 180 to 200° C. for 12 to 20 hours; after the reaction is completed, it is naturally cooled to room temperature, filtered, and washed with anhydrous ethanol and deionized water 3 times each, and vacuum dried at 60 to 80° C. for 12 to 20 hours to obtain silver-doped alumina particles.
[0020] The application of silver-doped alumina designed by the present invention in high wear-resistant denture materials is intended to significantly improve the comprehensive performance of dentures from three aspects: mechanics, wear resistance and antibacterial. First, the introduction of silver-doped alumina phase can significantly enhance the mechanical properties of denture materials. Alumina itself has excellent hardness and strength, and the doping of silver ions can further improve its mechanical properties through the solid solution strengthening mechanism. Silver ions replace part of aluminum ions to form a solid solution, causing lattice distortion and stress field, hindering the movement of dislocations, thereby improving the strength and hardness of the material. In addition, the cracking of the silver-doped alumina precursor during sintering helps to form fine and uniform alumina grains, and improves the mechanical properties of the material through the fine grain strengthening mechanism. At the same time, the twin structure formed in the alumina matrix can provide an additional strengthening mechanism. The twin interface can hinder crack propagation, improve the fracture toughness of the material, and reduce the risk of brittle fracture. Secondly, the silver-doped alumina phase has excellent wear resistance. Alumina ceramics have high hardness and excellent wear resistance, and the doping of silver ions can further improve its wear resistance. The lattice distortion and stress field caused by silver ion doping can improve the hardness and resistance to plastic deformation of the material and reduce the material removal rate during wear. In addition, small and uniform alumina grains are conducive to the formation of dense and uniform microstructures, reducing stress concentration and material shedding during wear. The twin structure in the alumina matrix can also improve the material's fatigue wear resistance and extend the service life of the denture by hindering crack propagation. Finally, the silver-doped alumina phase also has excellent antibacterial properties. Silver ions are broad-spectrum antibacterial agents and have significant inhibitory effects on a variety of oral pathogens, such as Streptococcus mutans and Actinomycetes. Silver ions can bind to the thiol groups on the bacterial cell membrane, destroy the integrity of the cell membrane, cause the leakage of cell contents and cause bacterial death. At the same time, silver ions can also bind to bacterial DNA to inhibit bacterial replication and reproduction. The silver-doped alumina phase formed during the sintering process can serve as a reservoir for silver ions, slowly releasing silver ions in the oral environment to achieve long-term antibacterial effects. The dense and uniform microstructure of the silver-doped alumina phase can also reduce the adhesion and colonization of bacteria on the surface of the denture, reduce the formation of plaque biofilm, and prevent complications such as secondary caries and denture stomatitis. In addition, the coherent interface formed between the silver-doped alumina phase and the zirconium oxide phase in the present invention can significantly improve the bonding strength and stress transfer efficiency between the two phases, and synergistically enhance the mechanical properties of the denture material. The formation of the coherent interface also helps to inhibit the initiation and propagation of cracks at the interface, and improve the fracture toughness and reliability of the material. In summary, the application of the silver-doped alumina designed in the present invention in the high wear-resistant denture material can significantly improve the mechanical properties, wear resistance and antibacterial properties of the denture through the synergistic effect of multiple enhancement and antibacterial mechanisms, extend the service life of the denture, reduce the risk of secondary oral diseases, and greatly improve the quality of life of patients. Therefore, the material design has broad application prospects in the field of oral restoration.
[0021] It is worth noting that zirconia / titania nanocomposite rods and silver-doped alumina as denture reinforcement phases have different focuses and synergistic mechanisms in improving the wear resistance and antibacterial properties of dentures. In terms of wear resistance, zirconia / titania nanocomposite rods use the high hardness, high strength and high toughness of zirconia ceramics to provide a good wear resistance foundation for composite materials; nanoscale zirconia nanorods have high specific surface area and surface energy, which enhances the bonding with the denture matrix material and improves the overall mechanical properties; titanium oxide particles are evenly distributed on the surface of zirconia nanorods, forming a multi-level structure similar to corn cobs, further enhancing the wear resistance of the denture material; the semi-coherent interface formed between zirconia and titanium oxide is conducive to interface bonding and stress transfer, improving the wear resistance of the composite material. Silver-doped alumina improves the material's hardness and resistance to plastic deformation and reduces the material removal rate during wear through the high hardness and excellent wear resistance of alumina ceramics, as well as the lattice distortion and stress field caused by silver ion doping; the fine and uniform alumina grains form a dense and uniform microstructure, reducing stress concentration and material shedding during wear; the twin structure in the alumina matrix can hinder crack propagation and improve the material's fatigue wear resistance. In terms of antibacterial properties, zirconium oxide / titanium oxide nanocomposite rods mainly inhibit the attachment and reproduction of bacteria on the denture surface to a certain extent through the antibacterial properties of zirconium oxide and titanium oxide themselves, as well as the high specific surface area and active sites provided by the nanoscale composite structure, thereby enhancing the antibacterial effect of the material. Silver-doped alumina uses the broad-spectrum antibacterial effect of silver ions to play a significant inhibitory role by destroying the integrity of bacterial cell membranes and inhibiting bacterial replication and reproduction; the silver-doped alumina phase formed during the sintering process can serve as a reservoir of silver ions, slowly releasing silver ions in the oral environment to achieve long-term antibacterial effects; the dense and uniform microstructure of the silver-doped alumina phase can reduce the adhesion and colonization of bacteria on the surface of dentures and reduce the formation of plaque biofilms. In addition, zirconium oxide / titanium oxide nanocomposite rods and silver-doped alumina phases have a synergistic effect in improving the wear resistance of dentures. Both can enhance the mechanical properties of denture materials through different mechanisms and comprehensively improve the wear resistance of dentures; in terms of antibacterial, the synergistic effect of the two can more comprehensively and lastingly inhibit bacterial colonization and reproduction on the surface of dentures; the coherent interface formed between the zirconium oxide phase and the silver-doped alumina phase can significantly improve the bonding strength and stress transfer efficiency between the two phases, synergistically enhance the mechanical properties of denture materials, and inhibit the initiation and propagation of cracks at the interface, thereby improving the fracture toughness and reliability of the material. This multi-component, multi-scale, and multifunctional composite material design strategy provides new ideas and methods for the development of new high-performance, long-life, and antibacterial denture materials.
[0022] Furthermore, the sintering aid is magnesium oxide or yttrium oxide.
[0023] Furthermore, the adhesive is hydroxypropyl methylcellulose or polyvinyl alcohol or gelatin.
[0024] Furthermore, the solvent is tetrahydrofuran, ethanol or acetone.
[0025] Furthermore, the pigment is a mixture of one or more of cerium oxide, erbium oxide and neodymium oxide.
[0026] Furthermore, the dispersant is sodium polyacrylate or sodium dodecyl sulfate.
[0027] The present invention introduces a variety of key components and process parameters in the preparation process of high wear-resistant denture materials, aiming to optimize the comprehensive performance and processing performance of the materials. First, the addition of sintering aids such as magnesium oxide or yttrium oxide can significantly promote the densification of aluminum oxide and zirconium oxide matrices, promote material transfer and grain rearrangement by forming a liquid phase, reduce the sintering temperature, and inhibit abnormal grain growth, thereby obtaining a dense and uniform microstructure and improving the mechanical properties and reliability of the material. Secondly, using hydroxypropyl methylcellulose, polyvinyl alcohol or gelatin as a molding aid can significantly improve the rheological properties and molding properties of the slurry. These polymer binders can increase the viscosity and plasticity of the slurry, give the green body sufficient strength, and completely decompose during the sintering process without affecting the performance of the material. Thirdly, tetrahydrofuran, ethanol or acetone are selected as dispersants, which can significantly improve the dispersibility and uniformity of ceramic powders in the slurry. These organic solvents have excellent solubility and volatility, can effectively avoid powder agglomeration, and volatilize quickly during the drying process without affecting the subsequent sintering process. Finally, by adding rare earth element pigments such as cerium oxide, erbium oxide, and neodymium oxide, the color tone and aesthetic properties of the denture material can be adjusted. These pigments have excellent coloring ability and chemical stability, can maintain color during high-temperature sintering, give the denture realistic color and transparency, and meet the aesthetic needs of patients. In summary, the present invention can significantly improve the comprehensive performance and processing performance of high-wear-resistant denture materials by rationally selecting key components such as sintering aids, molding aids, dispersants, and pigments, and optimizing the slurry preparation and molding process, thereby improving the clinical application effect of dentures and patient satisfaction.
[0028] The present invention also provides a method for preparing a 3D printed high-wear-resistant denture, which comprises the following steps:
[0029] S1: Denture data modeling: Scan the missing teeth in the patient's mouth, optimize and adjust the data to create the three-dimensional shape data of the denture digital model, and send it to the 3D printer for printing.
[0030] S2: Preparation of denture slurry: Mix zirconia / titania nanocomposite rods, silver-doped alumina particles, nano zirconia powder, dispersant and solvent, stir at 150-220 rpm for 2-4 hours, then continue to add sintering aid, adhesive and pigment and continue stirring for 30-60 minutes to obtain uniformly dispersed denture slurry.
[0031] S3: Printing denture blank: Put the evenly mixed denture slurry into the 3D printing device, set the printing parameters according to the data modeling, and then print and solidify the layers. After printing, clean and dry them in turn to obtain the denture blank.
[0032] S4: Sintering denture: Sintering the denture blank dried in step S3, and then grinding and polishing to obtain a highly wear-resistant denture.
[0033] Furthermore, the sintering parameters of step S4 are: firstly heating to 500-560°C at 1°C / min and keeping warm for 1-2.5h, then heating to 750-800°C at the same heating rate and keeping warm for 2h, then heating to 1400-1450°C at 2°C / min and keeping warm for 6-9h, and finally cooling to room temperature.
[0034] (3) Beneficial technical effects
[0035] 1. The present invention provides a design scheme of zirconium oxide / titanium oxide nanocomposite rods as 3D printing denture reinforcement materials, which has the following beneficial effects: first, the excellent mechanical properties of zirconium oxide ceramics, such as high hardness, high strength and high toughness, provide a good wear resistance foundation for the composite material, while the higher specific surface area and surface energy of nanoscale zirconium oxide nanorods enhance the bonding with the denture matrix material, further improving the overall mechanical properties; second, the corn cob-like multi-level structure formed by the uniform distribution of titanium oxide particles on the surface of the zirconium oxide nanorods, and the semi-coherent interface formed between zirconium oxide and titanium oxide are expected to further enhance the wear resistance of the denture material; third, the antibacterial properties of zirconium oxide and titanium oxide themselves, as well as the high specific surface area and more active sites provided by the nanocomposite structure, help to inhibit the attachment and reproduction of bacteria on the denture surface to a certain extent, and enhance the antibacterial effect of the material; finally, the good biocompatibility of zirconium oxide and titanium oxide can reduce the irritation and adverse reactions of dentures to oral tissues. In summary, the zirconium oxide / titanium oxide nanocomposite rod designed in the present invention is used as a reinforcing material for 3D printed dentures. Through the design of nanocomposite and multi-level structure, it improves the wear resistance and antibacterial properties of the denture while maintaining good biocompatibility, providing a new solution for the development of high-performance dentures and has broad application prospects.
[0036] 2. Silver-doped alumina has the following beneficial effects in high wear-resistant denture materials: First, the introduction of silver-doped alumina phase significantly enhances the mechanical properties of denture materials through mechanisms such as solid solution strengthening, fine grain strengthening and twin strengthening; secondly, the silver-doped alumina phase improves the hardness and resistance to plastic deformation of the material by virtue of the high hardness of alumina ceramics and the lattice distortion and stress field caused by silver ion doping, and combines the dense and uniform microstructure and twin structure to give the material excellent wear resistance; thirdly, the silver-doped alumina phase utilizes the broad-spectrum antibacterial effect of silver ions, which exerts a significant antibacterial effect by destroying the integrity of bacterial cell membranes and inhibiting bacterial replication and reproduction, and can slowly release silver ions to achieve long-term antibacterial effects; finally, the coherent interface formed between the silver-doped alumina phase and the zirconia phase synergistically enhances the mechanical properties of the denture material and inhibits the initiation and propagation of interface cracks. In summary, the application of silver-doped alumina designed in the present invention in high wear-resistant denture materials significantly improves the mechanical, wear-resistant and antibacterial properties of dentures through the synergistic effect of multiple enhancement and antibacterial mechanisms, and has broad application prospects in the field of oral restoration.
[0037] 3. In the preparation of high wear-resistant denture materials, the present invention introduces sintering aids (magnesium oxide or yttrium oxide) to promote densification, uses molding aids (hydroxypropyl methylcellulose, polyvinyl alcohol or gelatin) to improve rheology and molding properties, selects dispersants (tetrahydrofuran, ethanol or acetone) to improve the dispersion and uniformity of ceramic powders, and adds rare earth element pigments (cerium oxide, erbium oxide, neodymium oxide, etc.) to adjust the color tone and aesthetic properties. By rationally selecting key components and optimizing slurry preparation and molding processes, the comprehensive performance and processing performance of high wear-resistant denture materials are significantly improved, and the comprehensive performance of dentures is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a scanning electron microscope (SEM) morphology image of the zirconium oxide nanorods prepared in Example 1 of the present invention.
[0039] Figure 2 This is a scanning electron microscope (SEM) morphology image of the zirconium oxide / titanium oxide nanocomposite rod prepared in Example 1 of the present invention.
[0040] Figure 3 This is the XRD phase analysis diagram of the zirconium oxide nanorods prepared in Example 1 of the present invention.
[0041] Figure 4 XRD phase analysis diagram of zirconium oxide / titanium oxide nanocomposite rods prepared in Example 1 of the present invention.
[0042] Figure 5 This is a surface scan element distribution diagram of silver-doped aluminum oxide prepared in Example 1 of the present invention.
[0043] Figure 6Silver-doped alumina phase / zirconium oxide interface prepared in Example 1 of the present invention.
[0044] Figure 7 The zirconium oxide / titanium oxide interface prepared in Example 1 of the present invention.
[0045] Figure 8 The twin structure in the silver-doped alumina phase prepared in Example 1 of the present invention.
[0046] Fig. 9 This is a real picture of the highly wear-resistant denture prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0047] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0048] In the absence of specific conditions, the operations in the examples are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. Parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0049] Table 1 Reagents required for the examples and comparative examples and the corresponding purchasing companies
[0050] Tetrabutyl titanate company Anhydrous ethanol Shandong West Asia Chemical Co., Ltd. Zirconium oxychloride Shandong Mantanghong New Materials Co., Ltd. Cyclohexane Suzhou Qihang Biotechnology Co., Ltd. Polyoxyethylene Cocoate Shandong Mantanghong New Materials Co., Ltd. Silver acetate Shanghai MacLean Biochemical Technology Co., Ltd. N-Methylpyrrolidone Shanghai Anpu Laboratory Technology Co., Ltd. Methylaluminoxane Shanghai MacLean Biochemical Technology Co., Ltd. Magnesium Oxide Shandong West Asia Chemical Co., Ltd. Yttrium Oxide Shandong Mantanghong New Materials Co., Ltd. Hydroxypropyl methylcellulose Zhejiang Hangyu Pharmaceutical Technology Co., Ltd. Polyvinyl alcohol Shandong West Asia Chemical Co., Ltd. gelatin Sinopharm Chemical Reagent Co., Ltd. Tetrahydrofuran Shanghai MacLean Biochemical Technology Co., Ltd. Ethanol or acetone Guangzhou Yuanda New Materials Co., Ltd. Cerium Oxide Shandong West Asia Chemical Co., Ltd. Erbium Oxide Shanghai MacLean Biochemical Technology Co., Ltd. Neodymium Oxide Jiangsu Qiangsheng Functional Chemicals Co., Ltd.
[0051] Example 1
[0052] A 3D printed high-wear-resistant denture is prepared from the following components in parts by weight: 25 parts of zirconium oxide / titanium oxide nanocomposite rods, 10 parts of silver-doped alumina particles, 40 parts of nano zirconium oxide powder, 2 parts of magnesium oxide, 6 parts of hydroxypropyl methylcellulose, 3 parts of sodium polyacrylate, 15 parts of tetrahydrofuran, and 0.3 parts of cerium oxide.
[0053] The average length of the zirconium oxide / titanium oxide nanocomposite rods in this embodiment is 300 nm, and the average diameter is 80 nm.
[0054] The zirconium oxide / titanium oxide nanocomposite rods of this embodiment are composed of zirconium oxide nanorods and titanium oxide particles evenly distributed on the surface thereof, forming a structure similar to corn kernels on a corn cob. The diameter of the titanium oxide particles of this embodiment is 10 nm.
[0055] The titanium oxide particles of the present embodiment are in-situ grown on the zirconium oxide nanorods under a hydrothermal reaction; the interface between zirconium oxide and titanium oxide is a semi-coherent interface; the high wear-resistant denture contains a silver-doped alumina phase, which is produced by the cracking of the silver-doped alumina precursor during the sintering process, and the silver doping atomic percentage of the present embodiment is 0.2 at.%.
[0056] The silver-doped alumina phase of this embodiment contains a twin structure; and the interface between the silver-doped alumina phase and the zirconium oxide phase contains a coherent interface.
[0057] The preparation method of the zirconium oxide / titanium oxide nanocomposite rods of this embodiment is as follows: after 4 parts of tetrabutyl titanate and 80 parts of anhydrous ethanol are mixed evenly by weight, 30 parts of zirconium oxide nanorods are added thereto, and a uniform mixed solution is obtained after magnetic stirring for 30 minutes, which is then added to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 200° C. for 12 hours for hydrothermal reaction. After the reaction is completed, the mixed solution is filtered, washed with deionized water three times, and the filtered product is dried in a vacuum oven at 60° C. for 10 hours to obtain the zirconium oxide / titanium oxide nanocomposite rods.
[0058] The preparation method of the zirconium oxide nanorods of the present embodiment is as follows: in parts by weight, 10 parts of zirconium oxychloride, 2 parts of cyclohexane, 3 parts of polyoxyethylene coconut oil ester and 30 parts of 10% sodium hydroxide solution are mixed, and stirred for 3 hours under magnetic stirring to obtain a precipitated mixed solution, and then the mixed solution is centrifuged, the precipitate is dried at room temperature, and then heat-treated at 800° C. for 3 hours in an air atmosphere, and then the zirconium oxide nanorods are obtained after cooling.
[0059] The preparation method of the silver-doped alumina particles of the present embodiment is as follows: by weight, 24 parts of silver acetate and 120 parts of N-methylpyrrolidone are mixed and ultrasonically dispersed for 15 minutes to obtain a uniform dispersion of silver acetate in N-methylpyrrolidone; then, 12 parts of methylaluminoxane are slowly added to the above-mentioned mixed solution, and then magnetically stirred for 30 minutes to obtain a silver-doped alumina precursor solution; the silver-doped alumina precursor solution is transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, sealed, and hydrothermally reacted at 180°C for 12 hours; after the reaction is completed, it is naturally cooled to room temperature, filtered, and washed with anhydrous ethanol and deionized water for 3 times each, and vacuum dried at 60°C for 12 hours to obtain silver-doped alumina particles.
[0060] This embodiment also provides a method for preparing a 3D printed high-wear-resistant denture, which comprises the following steps:
[0061] S1: Denture data modeling: Scan the missing teeth in the patient's mouth, optimize and adjust the data to create the three-dimensional shape data of the denture digital model, and send it to the 3D printer for printing.
[0062] S2: Preparation of denture slurry: Mix zirconia / titania nanocomposite rods, silver-doped alumina particles, nano zirconia powder, dispersant and solvent, stir at 150 rpm for 2 h, then continue to add sintering aid, adhesive and pigment and continue stirring for 30 min to obtain uniformly dispersed denture slurry.
[0063] S3: Printing denture blank: Put the evenly mixed denture slurry into the 3D printing device, set the printing parameters according to the data modeling, and then print and solidify the layers. After printing, clean and dry them in turn to obtain the denture blank.
[0064] S4: Sintering denture: Sinter the denture blank dried in step S3, and finally obtain a highly wear-resistant denture after sintering and polishing. The sintering parameters are: first increase the temperature to 500°C at 1°C / min and keep it for 1 hour, then increase the temperature to 750°C at the same heating rate and keep it for 2 hours, then increase the temperature to 1400°C at 2°C / min and keep it for 6 hours, and finally cool it to room temperature.
[0065] according to Figure 1-8 The characterization results shown in FIG. 1 can be used to draw the following conclusions: Example 1 of the present invention successfully prepared a zirconium oxide / titanium oxide nanocomposite rod composed of zirconium oxide nanorods and titanium oxide particles uniformly distributed on the surface thereof, forming a structure similar to corn kernels on a corn cob ( Figure 1 and Figure 2 ). XRD phase analysis proves that zirconia nanorods are a single phase ( Figure 3 ), while the zirconia / titanium oxide nanocomposite rods contain two phases of zirconia and titanium oxide ( Figure 4 In addition, Example 1 also prepared a silver-uniformly doped aluminum oxide phase ( Figure 5 ), and formed a semi-coherent interface between the alumina phase and the zirconia phase ( Figure 6 ), there is also a semi-coherent interface between zirconium oxide and titanium oxide ( Figure 7 ) and the twin structure in silver-doped alumina ( Figure 8 Finally, Example 1 successfully prepared a highly wear-resistant denture using the above nanocomposite material ( Fig. 9 ). In summary, Example 1 of the present invention achieves the preparation of high-performance denture materials by constructing a nanocomposite structure and regulating the phase interface.
[0066] Example 2
[0067] A 3D printed high-wear-resistant denture is prepared from the following components in parts by weight: 30 parts of zirconium oxide / titanium oxide nanocomposite rods, 14 parts of silver-doped alumina particles, 53 parts of nano zirconium oxide powder, 3 parts of yttrium oxide, 8 parts of polyvinyl alcohol, 4 parts of sodium polyacrylate, 19 parts of ethanol, and 0.6 parts of erbium oxide.
[0068] The zirconium oxide / titanium oxide nanocomposite rods of this embodiment have an average length of 390 nm and an average diameter of 95 nm.
[0069] The zirconium oxide / titanium oxide nanocomposite rods of this embodiment are composed of zirconium oxide nanorods and titanium oxide particles evenly distributed on the surface thereof, forming a structure similar to corn kernels on a corn cob. The diameter of the titanium oxide particles of this embodiment is 14 nm.
[0070] The titanium oxide particles of the present embodiment are in-situ grown on the zirconium oxide nanorods under a hydrothermal reaction; the interface between zirconium oxide and titanium oxide is a semi-coherent interface; the high wear-resistant denture contains a silver-doped alumina phase, which is produced by the cracking of the silver-doped alumina precursor during the sintering process, and the silver doping atomic percentage of the present embodiment is 0.3 at.%.
[0071] The silver-doped alumina phase of this embodiment contains a twin structure; and the interface between the silver-doped alumina phase and the zirconium oxide phase contains a coherent interface.
[0072] The preparation method of the zirconium oxide / titanium oxide nanocomposite rods of this embodiment is as follows: after uniformly mixing 6 parts of tetrabutyl titanate and 87 parts of anhydrous ethanol by weight, 37 parts of zirconium oxide nanorods are added thereto, and a uniform mixed solution is obtained after magnetic stirring for 41 minutes, which is then added to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 215°C for 15 hours for hydrothermal reaction. After the reaction is completed, the mixed solution is filtered, washed with deionized water three times, and the filtered product is dried in a vacuum oven at 67°C for 14 hours to obtain the zirconium oxide / titanium oxide nanocomposite rods.
[0073] The preparation method of the zirconium oxide nanorods of the present embodiment is as follows: 13 parts of zirconium oxychloride, 3 parts of cyclohexane, 5 parts of polyoxyethylene coconut oil and 36 parts of 10% sodium hydroxide solution are mixed by weight, stirred for 5 hours under magnetic stirring, and then a precipitated mixed solution is obtained. Subsequently, the mixed solution is centrifuged, and the precipitate is dried at room temperature, and then heat-treated at 835° C. for 5 hours in an air atmosphere, and then the zirconium oxide nanorods are obtained after cooling.
[0074] The preparation method of the silver-doped alumina particles in this embodiment is as follows: 3 parts of silver acetate and 120 parts of N-methylpyrrolidone are mixed by weight, and then ultrasonically dispersed for 20 minutes to obtain a uniform dispersion of silver acetate in N-methylpyrrolidone; then, 15 parts of methylaluminoxane are slowly added to the above-mentioned mixed solution, and then magnetically stirred for 41 minutes to obtain a silver-doped alumina precursor solution; the silver-doped alumina precursor solution is transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, sealed, and hydrothermally reacted at 187°C for 15 hours; after the reaction is completed, it is naturally cooled to room temperature, filtered, and washed with anhydrous ethanol and deionized water for 3 times each, and vacuum dried at 67°C for 15 hours to obtain silver-doped alumina particles.
[0075] This embodiment also provides a method for preparing a 3D printed high-wear-resistant denture, which comprises the following steps:
[0076] S1: Denture data modeling: Scan the missing teeth in the patient's mouth, optimize and adjust the data to create the three-dimensional shape data of the denture digital model, and send it to the 3D printer for printing.
[0077] S2: Preparation of denture slurry: Zirconia / titania nanocomposite rods, silver-doped alumina particles, nano zirconium oxide powder, dispersant and solvent were mixed and stirred at 177 rpm for 3 h, and then sintering aid, adhesive and pigment were added and stirred for 41 min to obtain uniformly dispersed denture slurry.
[0078] S3: Printing denture blank: Put the evenly mixed denture slurry into the 3D printing device, set the printing parameters according to the data modeling, and then print and solidify the layers. After printing, clean and dry them in turn to obtain the denture blank.
[0079] S4: Sintering denture: Sinter the denture blank dried in step S3, and finally obtain a highly wear-resistant denture after sintering and polishing. The sintering parameters are: first increase the temperature to 521°C at 1°C / min and keep it for 1.5 hours, then increase the temperature to 768°C at the same heating rate and keep it for 2 hours, then increase the temperature to 1418°C at 2°C / min and keep it for 7 hours, and finally cool it to room temperature.
[0080] Example 3
[0081] A 3D printed high-wear-resistant denture is prepared from the following components in parts by weight: 31 parts of zirconium oxide / titanium oxide nanocomposite rods, 16 parts of silver-doped alumina particles, 61 parts of nano zirconium oxide powder, 4 parts of yttrium oxide, 10 parts of polyvinyl alcohol, 4 parts of sodium dodecyl sulfate, 21 parts of acetone, and 0.8 parts of neodymium oxide.
[0082] The zirconium oxide / titanium oxide nanocomposite rods of this embodiment have an average length of 450 nm and an average diameter of 104 nm.
[0083] The zirconium oxide / titanium oxide nanocomposite rods of this embodiment are composed of zirconium oxide nanorods and titanium oxide particles evenly distributed on the surface thereof, forming a structure similar to corn kernels on a corn cob. The diameter of the titanium oxide particles of this embodiment is 16 nm.
[0084] The titanium oxide particles of the present embodiment are in-situ grown on the zirconium oxide nanorods under a hydrothermal reaction; the interface between zirconium oxide and titanium oxide is a semi-coherent interface; the high wear-resistant denture contains a silver-doped alumina phase, which is produced by the cracking of the silver-doped alumina precursor during the sintering process, and the silver doping atomic percentage of the present embodiment is 0.4 at.%.
[0085] The silver-doped alumina phase of this embodiment contains a twin structure; and the interface between the silver-doped alumina phase and the zirconium oxide phase contains a coherent interface.
[0086] The preparation method of the zirconium oxide / titanium oxide nanocomposite rods of this embodiment is as follows: after 7 parts of tetrabutyl titanate and 92 parts of anhydrous ethanol are mixed evenly by weight, 42 parts of zirconium oxide nanorods are added thereto, and a uniform mixed solution is obtained after magnetic stirring for 48 minutes, which is then added to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 230°C for 17 hours for hydrothermal reaction. After the reaction is completed, the mixed solution is filtered, washed with deionized water three times, and the filtered product is dried in a vacuum oven at 72°C for 16 hours to obtain the zirconium oxide / titanium oxide nanocomposite rods.
[0087] The preparation method of the zirconium oxide nanorods of the present embodiment is as follows: 15 parts of zirconium oxychloride, 3 parts of cyclohexane, 6 parts of polyoxyethylene coconut oil and 39 parts of 10% sodium hydroxide solution are mixed by weight, stirred for 6 hours under magnetic stirring, and then a precipitated mixed solution is obtained. Subsequently, the mixed solution is centrifuged, the precipitate is dried at room temperature, and then heat-treated at 860° C. for 5 hours in an air atmosphere, and then the zirconium oxide nanorods are obtained after cooling.
[0088] The preparation method of the silver-doped alumina particles in this embodiment is as follows: 3 parts of silver acetate and 120 parts of N-methylpyrrolidone are mixed by weight and then ultrasonically dispersed for 24 minutes to obtain a uniform dispersion of silver acetate in N-methylpyrrolidone; then, 17 parts of methylaluminoxane are slowly added to the above-mentioned mixed solution, and then magnetically stirred for 48 minutes to obtain a silver-doped alumina precursor solution; the silver-doped alumina precursor solution is transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, sealed, and hydrothermally reacted at 192°C for 17 hours; after the reaction is completed, it is naturally cooled to room temperature, filtered, and washed with anhydrous ethanol and deionized water for 3 times each, and vacuum dried at 72°C for 17 hours to obtain silver-doped alumina particles.
[0089] This embodiment also provides a method for preparing a 3D printed high-wear-resistant denture, which comprises the following steps:
[0090] S1: Denture data modeling: Scan the missing teeth in the patient's mouth, optimize and adjust the data to create the three-dimensional shape data of the denture digital model, and send it to the 3D printer for printing.
[0091] S2: Preparation of denture slurry: Zirconia / titania nanocomposite rods, silver-doped alumina particles, nano zirconium oxide powder, dispersant and solvent were mixed and stirred at 192 rpm for 3 h, and then sintering aid, adhesive and pigment were added and stirred for 48 min to obtain uniformly dispersed denture slurry.
[0092] S3: Printing denture blank: Put the evenly mixed denture slurry into the 3D printing device, set the printing parameters according to the data modeling, and then print and solidify the layers. After printing, clean and dry them in turn to obtain the denture blank.
[0093] S4: Sintering denture: Sinter the denture blank dried in step S3, and finally obtain a highly wear-resistant denture by grinding and polishing. The sintering parameters are: firstly heat to 536℃ at 1℃ / min and keep it for 1.9h, then heat to 780℃ at the same heating rate and keep it for 2h, then heat to 1430℃ at 2℃ / min and keep it for 8h, and finally cool to room temperature.
[0094] Example 4
[0095] A 3D printed high-wear-resistant denture is prepared from the following components in parts by weight: 40 parts of zirconium oxide / titanium oxide nanocomposite rods, 20 parts of silver-doped alumina particles, 75 parts of nano zirconium oxide powder, 5 parts of magnesium oxide, 12 parts of hydroxypropyl methylcellulose, 5 parts of sodium lauryl sulfate, 25 parts of solvent, 0.6 parts of cerium oxide and 0.6 parts of erbium oxide.
[0096] The average length of the zirconium oxide / titanium oxide nanocomposite rods in this embodiment is 550 nm, and the average diameter is 120 nm.
[0097] The zirconium oxide / titanium oxide nanocomposite rods of this embodiment are composed of zirconium oxide nanorods and titanium oxide particles evenly distributed on the surface thereof, forming a structure similar to corn kernels on a corn cob. The diameter of the titanium oxide particles of this embodiment is 20 nm.
[0098] The titanium oxide particles of the present embodiment are in-situ grown on the zirconium oxide nanorods under a hydrothermal reaction; the interface between zirconium oxide and titanium oxide is a semi-coherent interface; the high wear-resistant denture contains a silver-doped alumina phase, which is produced by the cracking of the silver-doped alumina precursor during the sintering process, and the silver doping atomic percentage of the present embodiment is 0.6 at.%.
[0099] The silver-doped alumina phase of this embodiment contains a twin structure; and the interface between the silver-doped alumina phase and the zirconium oxide phase contains a coherent interface.
[0100] The preparation method of the zirconium oxide / titanium oxide nanocomposite rods of the present embodiment is as follows: after uniformly mixing 9 parts of tetrabutyl titanate and 100 parts of anhydrous ethanol by weight, 50 parts of zirconium oxide nanorods are added thereto, and a uniform mixed solution is obtained after magnetic stirring for 60 minutes, and then the mixed solution is added to a polytetrafluoroethylene-lined stainless steel autoclave and kept at 250° C. for 20 hours for hydrothermal reaction. After the reaction is completed, the mixed solution is filtered, washed with deionized water for 3 times, and the filtered product is dried in a vacuum oven at 80° C. for 20 hours to obtain the zirconium oxide / titanium oxide nanocomposite rods.
[0101] The preparation method of the zirconium oxide nanorods of the present embodiment is as follows: by weight, 18 parts of zirconium oxychloride, 4 parts of cyclohexane, 8 parts of polyoxyethylene coconut oil ester and 45 parts of 10% sodium hydroxide solution are mixed, and stirred for 8 hours under magnetic stirring to obtain a precipitated mixed solution, and then the mixed solution is centrifuged, the precipitate is dried at room temperature, and then heat-treated at 900° C. for 7 hours in an air atmosphere, and then cooled to obtain the zirconium oxide nanorods.
[0102] The preparation method of the silver-doped alumina particles of the present embodiment is as follows: in parts by weight, 4 parts of silver acetate and 120 parts of N-methylpyrrolidone are mixed and ultrasonically dispersed for 30 minutes to obtain a uniform dispersion of silver acetate in N-methylpyrrolidone; then, 20 parts of methylaluminoxane are slowly added to the above-mentioned mixed solution, and magnetic stirring is performed for 60 minutes to obtain a silver-doped alumina precursor solution; the silver-doped alumina precursor solution is transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, sealed, and hydrothermally reacted at 200°C for 20 hours; after the reaction is completed, it is naturally cooled to room temperature, filtered, and washed with anhydrous ethanol and deionized water for 3 times each, and vacuum dried at 80°C for 20 hours to obtain silver-doped alumina particles.
[0103] This embodiment also provides a method for preparing a 3D printed high-wear-resistant denture, which comprises the following steps:
[0104] S1: Denture data modeling: Scan the missing teeth in the patient's mouth, optimize and adjust the data to create the three-dimensional shape data of the denture digital model, and send it to the 3D printer for printing.
[0105] S2: Preparation of denture slurry: Mix zirconia / titania nanocomposite rods, silver-doped alumina particles, nano zirconia powder, dispersant and solvent, stir at 220 rpm for 4 h, then continue to add sintering aid, adhesive and pigment and continue stirring for 60 min to obtain uniformly dispersed denture slurry.
[0106] S3: Printing denture blank: Put the evenly mixed denture slurry into the 3D printing device, set the printing parameters according to the data modeling, and then print and solidify the layers. After printing, clean and dry them in turn to obtain the denture blank.
[0107] S4: Sintering denture: Sinter the denture blank dried in step S3, and finally obtain a highly wear-resistant denture after sintering and polishing. The sintering parameters are: first increase the temperature to 560°C at 1°C / min and keep it for 2.5 hours, then increase the temperature to 800°C at the same heating rate and keep it for 2 hours, then increase the temperature to 1450°C at 2°C / min and keep it for 9 hours, and finally cool it to room temperature.
[0108] Example 5
[0109] The method is basically the same as Example 1, except that 40 parts of zirconium oxide / titanium oxide nanocomposite rods are added to prepare the wear-resistant denture.
[0110] Comparative Example 1
[0111] It is basically the same as Example 1, except that titanium oxide is not prepared on the surface of the zirconium oxide / titanium oxide nanocomposite rods added to prepare the wear-resistant denture, so an equal amount of zirconium oxide nanorods are added.
[0112] Comparative Example 2
[0113] It is basically the same as Example 1, except that the zirconium oxide nanorods and titanium oxide particles used in preparing wear-resistant dentures are added separately, so there is no binding relationship between the two.
[0114] Comparative Example 3
[0115] It is basically the same as Example 1, except that the aluminum oxide particles added to prepare the wear-resistant denture are not doped with silver elements.
[0116] Performance Test:
[0117] Wear resistance is one of the important indicators in the application of dentures. The UMT-2MT friction and wear tester is used to evaluate the wear resistance of denture materials. The tester can simulate the chewing movement in the mouth and accurately control the test parameters to obtain reliable wear data. The test uses a ball-surface contact friction pair. The ball material is Si with a diameter of 3 mm. 3 N 4 Ceramic ball, its hardness is 92HRA, Young's modulus is in the range of 290~330GPa. 3 N 4 Ceramic balls have excellent hardness and wear resistance, and can effectively simulate the wear of denture materials. The test conditions are as follows: the motion mode is reciprocating, the frequency is 2Hz, the amplitude is 2mm, the maximum number of cycles is 5500 times, and the normal load is 20N (the middle value of the normal chewing force range of 3 to 36N in the mouth). During the test, the prepared denture material sample is fixed on the workbench of the testing machine, and the Si is adjusted. 3 N 4 The contact position between the ceramic ball and the sample surface. After setting the test parameters, start the test machine to make the ceramic ball slide back and forth on the sample surface to simulate chewing motion. After reaching the preset maximum number of cycles, terminate the test. After the test, use equipment such as a surface roughness meter and a laser confocal microscope to observe and quantify the wear of the sample surface, such as wear volume, wear depth, surface roughness and other indicators. By comparing the data before and after the test, the wear resistance of the denture material is evaluated.
[0118] Hardness is also one of the important indicators in coating applications. The hardness is tested by nanoindentation. The instrument model for nanoindentation testing is G200, and the Poisson's ratio is set to 0.25.
[0119] Antibacterial property: The antibacterial property of dentures was evaluated by optical density method, by measuring the amount of Staphylococcus aureus and Escherichia coli attached to the surface of the material. First, a high-concentration bacterial solution was prepared and its initial OD value (450nm wavelength) was obtained. Then, the bacterial solution was diluted step by step and the OD value was measured to construct a standard curve of OD and colony number and its correlation coefficient R. Next, the sterilized denture base sample was immersed in the bacterial solution. After incubation, the bacteria were ultrasonically treated to separate into physiological saline, the OD value of the bacterial suspension was measured, the bacterial concentration was calculated based on the standard curve, and finally the antibacterial efficiency of the material was calculated.
[0120] The properties of the dentures of Examples 1 to 5 and Comparative Examples 1 to 3 are summarized in Table 2.
[0121] Table 2 Performance of the dentures of Examples 1 to 5 and Comparative Examples 1 to 3
[0122]
[0123] The core difference between Comparative Example 1 and Example 1 is whether a titanium oxide layer is prepared on the surface of the zirconium oxide nanorods. The data in Table 2 clearly show that this subtle change significantly improves the wear resistance, hardness and antibacterial properties of the denture. Specifically, the high hardness and wear resistance of titanium oxide form a solid barrier on the surface of zirconium oxide nanorods, effectively resisting the wear of daily use, optimizing the interfacial bonding force, and enhancing the overall stability of the denture. At the same time, the antibacterial properties of titanium oxide give the denture surface the ability to inhibit bacterial growth, which helps maintain oral health. In summary, the introduction of titanium oxide is a key factor in improving the comprehensive performance of dentures.
[0124] The main difference between Comparative Example 2 and Example 1 is whether the zirconium oxide nanorods and titanium oxide particles are in a combined state, and whether there is a semi-coherent interface between them. It can be clearly seen from the data in Table 2 that when the zirconium oxide nanorods and titanium oxide particles are combined into zirconium oxide / titanium oxide nanocomposite rods, the wear resistance and hardness of the denture are significantly improved. This phenomenon is mainly attributed to the semi-coherent interface formed in the combined state, which not only enhances the interaction force between zirconium oxide and titanium oxide, so that the two can work together as a whole and jointly withstand external stress, but also optimizes the microstructure of the material, so that the composite material can more effectively disperse and resist stress when worn, thereby extending the service life of the denture. In addition, this combined state also promotes the uniform distribution of stress inside the material, reduces the phenomenon of aggravated wear caused by stress concentration, and further improves the wear resistance of the denture.
[0125] The main difference between Comparative Example 3 and Example 1 is whether silver is doped into the alumina particles. It can be clearly seen from the data in Table 2 that silver-doped alumina significantly improves the wear resistance, hardness and antibacterial properties of the denture. This is because the doping of silver in alumina, on the one hand, enhances the mechanical properties of the alumina matrix through its own hardness and wear resistance, so that the denture can more effectively resist wear and deformation when subjected to external stress. On the other hand, the silver element also has good antibacterial properties, which can inhibit the growth and reproduction of bacteria in the oral cavity, thereby reducing bacterial erosion and damage to the denture, and protecting the integrity and service life of the denture. Therefore, while silver-doped alumina improves the wear resistance and hardness of the denture, it also gives the denture excellent antibacterial properties.
[0126] In summary, the present invention designs zirconium oxide / titanium oxide nanocomposite rods as 3D printed denture reinforcement materials, combines the high mechanical properties of zirconium oxide and the strengthening effect of titanium oxide to form a multi-level structure to enhance wear resistance, and uses the antibacterial properties and biocompatibility of the two to improve the comprehensive performance of dentures, providing a new path for the development of high-performance dentures. Silver-doped alumina improves the mechanical properties of highly wear-resistant denture materials through solid solution, fine crystals and twin strengthening, combines high hardness with the antibacterial properties of silver ions to achieve a dual improvement in wear resistance and long-term antibacterial properties, and forms a coherent interface with zirconium oxide to enhance the overall performance, showing broad application prospects in the field of oral restoration. At the same time, the present invention uses sintering and molding aids to optimize densification and molding properties in the preparation of highly wear-resistant denture materials, dispersants to improve the uniformity of ceramic powders, and rare earth elements to regulate aesthetic properties. The comprehensive performance and processing performance of denture materials are significantly improved through key component selection and process optimization.
[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A 3D printed high wear-resistant denture, characterized in that: The invention is prepared from the following components in parts by weight: 25-40 parts of zirconium oxide / titanium oxide nanocomposite rods, 10-20 parts of silver-doped alumina particles, 40-75 parts of nano zirconium oxide powder, 2-5 parts of sintering aid, 6-12 parts of adhesive, 3-5 parts of dispersant, 15-25 parts of solvent, and 0.3-1.2 parts of pigment; The zirconium oxide / titanium oxide nanocomposite rods have an average length of 300-550 nm and an average diameter of 80-120 nm; The zirconium oxide / titanium oxide nanocomposite rods are composed of zirconium oxide nanorods and titanium oxide particles evenly distributed on the surface thereof, forming a structure similar to corn kernels on a corn cob, and the titanium oxide particles have a diameter of 10 to 20 nm; The titanium oxide particles are in-situ grown on the zirconium oxide nanorods under a hydrothermal reaction; The interface between the zirconium oxide and the titanium oxide is a semi-coherent interface; The highly wear-resistant denture contains a silver-doped alumina phase, which is produced by the sintering process of silver-doped alumina particles, and the silver doping atomic percentage is 0.2-0.6 at.%; The silver-doped aluminum oxide phase contains a twin structure; The interface between the silver-doped aluminum oxide phase and the zirconium oxide phase contains a coherent interface; The preparation method of the zirconium oxide / titanium oxide nanocomposite rod is as follows: after 4 to 9 parts of tetrabutyl titanate and 80 to 100 parts of anhydrous ethanol are mixed uniformly by weight, 30 to 50 parts of zirconium oxide nanorods are added thereto, magnetically stirred for 30 to 60 minutes to obtain a uniform mixed solution, then added into a polytetrafluoroethylene-lined stainless steel autoclave, and kept at 200 to 250° C. for 12 to 20 hours for hydrothermal reaction, after the reaction is completed, the mixed solution is filtered, washed with deionized water for 3 times, and the filtered product is dried in a vacuum oven at 60 to 80° C. for 10 to 20 hours to obtain the zirconium oxide / titanium oxide nanocomposite rod; The preparation method of the zirconium oxide nanorods is as follows: by weight, 10 to 18 parts of zirconium oxychloride, 2 to 4 parts of cyclohexane, 3 to 8 parts of polyoxyethylene coconut oil ester and 30 to 45 parts of a sodium hydroxide solution with a mass fraction of 10% are mixed, and stirred for 3 to 8 hours under magnetic stirring to obtain a precipitated mixed solution, and then the mixed solution is centrifuged, the precipitate is dried at room temperature, and then heat-treated at 800 to 900° C. for 3 to 7 hours in an air atmosphere, and then cooled to obtain the zirconium oxide nanorods; The preparation method of the silver-doped alumina particles is as follows: by weight, 2 to 4 parts of silver acetate and 120 parts of N-methylpyrrolidone are mixed and ultrasonically dispersed for 15 to 30 minutes to obtain a uniform dispersion of silver acetate in N-methylpyrrolidone; subsequently, 12 to 20 parts of methylaluminoxane are slowly added to the mixed solution, and then magnetically stirred for 30 to 60 minutes to obtain a silver-doped alumina precursor solution; the silver-doped alumina precursor solution is transferred to a stainless steel high-pressure reactor lined with polytetrafluoroethylene, sealed, and hydrothermally reacted at 180 to 200° C. for 12 to 20 hours; after the reaction is completed, it is naturally cooled to room temperature, filtered, and washed with anhydrous ethanol and deionized water for 3 times each, and vacuum dried at 60 to 80° C. for 12 to 20 hours to obtain silver-doped alumina particles.
2. A 3D printed high wear-resistant denture as claimed in claim 1, characterized in that: The sintering aid is magnesium oxide or yttrium oxide; The adhesive is hydroxypropyl methylcellulose or polyvinyl alcohol or gelatin.
3. A 3D printed high wear-resistant denture as claimed in claim 1, characterized in that: The solvent is tetrahydrofuran, ethanol or acetone; The pigment is a mixture of one or more of cerium oxide, erbium oxide and neodymium oxide; The dispersant is sodium polyacrylate or sodium dodecyl sulfate.
4. A method for preparing a 3D printed high-wear-resistant denture according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1: Denture data modeling: Scan the missing teeth in the patient's mouth, optimize and adjust the data to create the three-dimensional shape data of the denture digital model, and send it to the 3D printer for printing; S2: preparing denture slurry: mixing zirconia / titania nanocomposite rods, silver-doped alumina particles, nano zirconia powder, dispersant and solvent, stirring at 150-220 rpm for 2-4 h, then adding sintering aid, adhesive and pigment and stirring for 30-60 min to obtain uniformly dispersed denture slurry; S3: Printing denture blank: Put the mixed denture slurry into the 3D printing device, set the printing parameters according to the data modeling, and then print and solidify layer by layer. After printing, clean and dry in turn to obtain the denture blank; S4: Sintering the denture: Sintering the denture blank dried in step S3, and then grinding and polishing the denture to obtain a highly wear-resistant denture.
5. The method for preparing a 3D printed high-wear-resistant denture according to claim 4, characterized in that: The sintering parameters of step S4 are: firstly heating to 500-560°C at 1°C / min and keeping at that temperature for 1-2.5h, then heating to 750-800°C at the same heating rate and keeping at that temperature for 2h, then heating to 1400-1450°C at 2°C / min and keeping at that temperature for 6-9h, and finally cooling to room temperature.
Citation Information
Patent Citations
Method for silver-doped aluminum oxide antibacterial powder through hydrothermal method one-off synthesis
CN105127444A
Nano composite resin for dental repair and preparation method thereof
CN109481317A
Preparation method of nano TiO2 / ZrO2 composite catalyst
CN110586058A
3D printed zirconium oxide-based false tooth material and preparation method thereof
CN111704457A